Video streaming industry: how can streaming video companies increase customer re-purchase intention in Portugal - Champalimaud, Maria João Baginski (2024)
The burgeoning expansion of video streaming has profoundly disrupted traditional television. A compelling topic emerges as the industry undergoes dynamic transformations, and understanding customer repurchase intention is vital for sustained business success. Focused on Portugal, the research investigates strategies for enhancing repurchase intention among five prominent brands – Netflix, HBO Max, Disney +, Amazon Prime Video, and Apple TV +. To perform this study, two analytical approaches were used, conjoint and perceptual maps analysis, delineating preferences, and perceptions regarding the aforementioned brands and emphasizing attributes as account sharing and show virality, with potential dispersion in preferences mitigated through strategic technological innovation.